Answer:
what is the question
Step-by-step explanation:
Answer:
x can be cancelled
Step-by-step explanation:
we are given
![\frac{4x^3-10x^2+6x}{2x^3+x^2-3x}](https://tex.z-dn.net/?f=%5Cfrac%7B4x%5E3-10x%5E2%2B6x%7D%7B2x%5E3%2Bx%5E2-3x%7D)
Firstly, we will factor numerator and denominator
and then we can factor it
![4x^3-10x^2+6x=2x(2x^2-5x+3)](https://tex.z-dn.net/?f=4x%5E3-10x%5E2%2B6x%3D2x%282x%5E2-5x%2B3%29)
![4x^3-10x^2+6x=2x(2x+1)(x-3)](https://tex.z-dn.net/?f=4x%5E3-10x%5E2%2B6x%3D2x%282x%2B1%29%28x-3%29)
now, we can factor denominator
![2x^3+x^2-3x=x(2x^2+x-3)](https://tex.z-dn.net/?f=2x%5E3%2Bx%5E2-3x%3Dx%282x%5E2%2Bx-3%29)
![2x^3+x^2-3x=x(x-1)(2x+3)](https://tex.z-dn.net/?f=2x%5E3%2Bx%5E2-3x%3Dx%28x-1%29%282x%2B3%29)
now, we can replace it
![\frac{4x^3-10x^2+6x}{2x^3+x^2-3x}=\frac{2x(2x+1)(x-3)}{x(x-1)(2x+3)}](https://tex.z-dn.net/?f=%5Cfrac%7B4x%5E3-10x%5E2%2B6x%7D%7B2x%5E3%2Bx%5E2-3x%7D%3D%5Cfrac%7B2x%282x%2B1%29%28x-3%29%7D%7Bx%28x-1%29%282x%2B3%29%7D)
we can see that
both terms are having x common
so, x can be cancelled
So,
x can be cancelled
Answer:
Sorry if this doesnt make help:
Step-by-step explanation:
When two figures are similar, the ratios of the lengths of their corresponding sides are equal. To determine if the shapes are similar, compare their corresponding sides.
Rotation 90° translates (x, y) to (-y, x). Thus (3, 2) gets translated to (-2, 3). Your green box gets filled with -2.